The human anterior cruciate ligament: histological and ultrastructural observations. - Strocchi, R (1992)
In transverse and longitudinal paraffin-embedded sections, the human anterior cruciate ligament (ACL) is made up of wavy bundles of collagen fibres arrayed in various directions, the majority around the axis of the ligament with a few running parallel to it. The fascicles making up the larger bundles are also characterised by this undulating appearance. In thin sections 2 types of collagen fibrils are observed: small (with a single diameter peak at 45 nm) and large (3 peaks at 35, 50 and 75 nm respectively), organised into distinct areas made up of either large or small bundles of fibrils. The numerous fibroblasts that are present appear elongated in the direction of the bundles with branches and short cytoplasmic processes. The elastic system is made up of both elastic and oxytalan fibres. The varied orientation of the bundles in the ACL, the complex ultrastructural organisation and the abundant elastic system make it very different from other ligaments and tendons, providing a structure able to withstand the multiaxial stresses and varying tensile strains imposed upon it.